Descemetocele and bilateral, severe Pseudomonas keratitis in an intensive care unit patient with Graves' orbitopathy: A case report. Issue 40 (2nd October 2020) - Hsieh, Yun Chen; Chen, Chun-Chen
Abstract: Rationale: Exposure keratopathy (EK) is common among intensive care unit (ICU) patients, especially those under sedation and with incomplete eyelid closure. EK can be mild punctate epithelial erosions exhibiting spontaneous recovery; rarely, severe complications including bacterial ulcers causing corneal perforation or opacity could occur. We describe a patient with pre-existing Graves' orbitopathy (GO) who developed bilateral, rapidly progressing bacterial keratitis due to EK with secondary aerosol inoculation from respiratory pathogens in ICU. Patient concerns: A 49-year-old intubated and sedated woman who underwent urgent craniotomy was admitted to ICU. The ophthalmology department was consulted for progressive chemosis. History of poorly controlled GO was revealed based on external ocular signs, including proptosis with lid retraction, and careful ophthalmological history taking. After 2 days of ICU admission, slit lamp examination revealed large inferior corneal epithelial defects and dellen (OU). Despite prescribing gentamicin ointment and lubricants, purulent discharge with corneal infiltration and thinning (OU) was observed 2 days later. Owing to a characteristic Pseudomonas odor from her endotracheal tube, corneal and endotracheal sputum cultures were obtained, which revealed Pseudomonas aeruginosa infection. Diagnosis: Pseudomonas keratitis secondary to EK Interventions: Topical fortified anti- Pseudomonas antibiotic eye drops with temporary tarsorrhaphy and lubricants Outcomes: Despite multiple treatments, she developed enlarging descemetocele in the left eye with severe corneal stromal destruction and severe visual impairment due to central corneal scar formation in the right eye. After 2 months, the descemetocele ruptured owing to generalized tonic–clonic seizures after cranioplasty. Therefore, she underwent urgent penetrating keratoplasty in the left eye. Lessons: GO increases ocular surface inflammation and exposure, which may exacerbate EK and subsequent complication risks. Careful monitoring and aggressive treatment through appropriate eye care regimen are required in these patients.